Analisis Stakeholder Kebijakan E-Katalog Lokal dalam Membranding Produk Lokal - Binti Azizatun Nafi’ah (Public Administration Dept, Faculty of Social and Political Science, 2022)
A country certainly has ways and efforts to increase the effectiveness and productivity of the country's economy. The needs of consumers, producers and the allocation of goods for facilities and infrastructure to provide public services must be carried out through the process of procurement of goods/services. This procurement effort is aimed at building economic growth through procurement of goods so that it is more effective and efficient. The purpose of this study is to analyze local e-catalog policies in local product marketing (MSMEs) in terms of SWOT, as well as identify supporting and inhibiting factors for the effectiveness of these policies. The method used is a literature review method. The data collection technique used is literature study, which utilizes journal articles, newspapers, books, online news and websites of authoritative institutions. The result of this research is that local e-kalalog can help MSMEs as business actors who generally utilize local resources, be it human resources, capital, raw materials, to equipment. This means that most of the needs of MSMEs do not rely on imported goods. In this local e-catalogue, the regional head, ULP, legal department, and the inspectorate are the key players who have big interests and influence, while MSMEs and SKPD are supporting parts that have small interests but have a big impact.